Bersama Melawan Virus Covid 19 di Indonesia - Syafrida Syafrida; Ralang Hartati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractCovid-19 hit many countries in the world including Indonesia. The Covid-19 outbreak is not only a national problem in a country, but already a global problem. Covid-19 originated in the Wuhan area of China. The spread of Covid-19 is so fast and deadly, transmission through physical contact is transmitted through the mouth, eyes and nose. Covid-19 has an impact on social life and the weakening of the people's economy. The issue of how the impact of the Covid-19 outbreak on public services and efforts to overcome the Covid-19 outbreak. The juridical normative research method is supported by empirical research using secondary data in the form of books, legislation and the internet. Type of qualitative research. The results of the study concluded that the impact of the Covid-19 outbreak caused social problems to weaken the economy of the community and the state. To prevent the spread of the Covid-19 outbreak, it needed the cooperation of governments, communities, religious leaders to help one another help, help one another and remind one another to deepen Covid-19.Keywords: Fight, Covid-19, Indonesia AbstrakCovid-19 melanda banyak Negara di dunia termasuk Indonesia. Wabah Covid-19 tidak hanya merupakan masalah nasional dalam suatu Negara, tapi sudah merupakan masalah global. Covid-19 berawal muncul dari daerah Wuhan Cina. Penyebaran Covid -19 yang begitu cepat dan mematikan,, penularannya melalui kontak fisik ditularkan melalui mulut, mata dan hidung. Covid-19 berdampak kepada kehidupan sosial dan melemahnya ekonomi masyarakat. Permasalahan bagaimana dampak wabah Covid-19 terhadap pelayanan publik dan upaya penanggulangan wabah Covid-19. Metode penelitian bersifat yuridis normatif yang didukung penelitian empiris menggunakan data sekunder berupa buku-buku, peraturan perundangan-undangan dan internet. Jenis penelitian kualitatif. Hasil penelitian disimpulkan dampak wabah Covid-19 menimbulkan masalah sosial pelemahan ekonomi masyarakat dan negara, Untuk mencegah penyebaran wabah Covid- 19  diperlukan kerja sama pemerintah, masyarakat, tokoh agama untuk saling bantu membatu, bahu membahu dan mengingatkan satu sama lainnya bersama melawan Covid-19. Kata kunci: Melawan, Covid-19, Indonesia.